2002
DOI: 10.1016/s0022-5347(05)64225-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Vesicoureteral Reflux: A 15-Year Perspective

Abstract: Grades I to III primary vesicoureteral reflux diagnosed after urinary tract infection resolve at identical rates and significantly more rapidly than grades IV to V. Early repair of grade IV to V reflux should be considered after age 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(46 citation statements)
references
References 17 publications
2
41
0
1
Order By: Relevance
“…A recent study reported that low-grade VUR (grades I to III) diagnosed after UTI resolves significantly more rapidly than does high-grade VUR (grades IV to V) [21]. Camacho et al [8] evaluated the prognostic value of DMSA renal scans performed during febrile UTI and reported that the frequency of VUR was higher by as much as 48% when the DMSA scan result was abnormal than the frequency of VUR when the DMSA scan result was normal in children (12%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that low-grade VUR (grades I to III) diagnosed after UTI resolves significantly more rapidly than does high-grade VUR (grades IV to V) [21]. Camacho et al [8] evaluated the prognostic value of DMSA renal scans performed during febrile UTI and reported that the frequency of VUR was higher by as much as 48% when the DMSA scan result was abnormal than the frequency of VUR when the DMSA scan result was normal in children (12%).…”
Section: Discussionmentioning
confidence: 99%
“…4, 5 However, recently studies have shown UTI, pyelonephritis, and renal scarring rates are not statistically different among VUR patients receiving AP and those not. 68 One possible explanation for these findings is patient noncompliance with AP.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of continuous antibiotic prophylaxis is to keep the urine “sterile” so that the risk of retrograde renal infection will be decreased. Since a significant proportion of reflux cases will spontaneously resolve with time, 4,5 many authors recommend a conservative approach, ie continuous antibiotic prophylaxis, as the initial management option in children, reserving surgical intervention for those in whom continuous antibiotic prophylaxis is ineffective at preventing urinary tract infection.…”
mentioning
confidence: 99%